If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 208 + -3x = x + (x + 1) + (x + 2) + (x + 3) + (x + 4) + -50 Reorder the terms: 208 + -3x = x + (1 + x) + (x + 2) + (x + 3) + (x + 4) + -50 Remove parenthesis around (1 + x) 208 + -3x = x + 1 + x + (x + 2) + (x + 3) + (x + 4) + -50 Reorder the terms: 208 + -3x = x + 1 + x + (2 + x) + (x + 3) + (x + 4) + -50 Remove parenthesis around (2 + x) 208 + -3x = x + 1 + x + 2 + x + (x + 3) + (x + 4) + -50 Reorder the terms: 208 + -3x = x + 1 + x + 2 + x + (3 + x) + (x + 4) + -50 Remove parenthesis around (3 + x) 208 + -3x = x + 1 + x + 2 + x + 3 + x + (x + 4) + -50 Reorder the terms: 208 + -3x = x + 1 + x + 2 + x + 3 + x + (4 + x) + -50 Remove parenthesis around (4 + x) 208 + -3x = x + 1 + x + 2 + x + 3 + x + 4 + x + -50 Reorder the terms: 208 + -3x = 1 + 2 + 3 + 4 + -50 + x + x + x + x + x Combine like terms: 1 + 2 = 3 208 + -3x = 3 + 3 + 4 + -50 + x + x + x + x + x Combine like terms: 3 + 3 = 6 208 + -3x = 6 + 4 + -50 + x + x + x + x + x Combine like terms: 6 + 4 = 10 208 + -3x = 10 + -50 + x + x + x + x + x Combine like terms: 10 + -50 = -40 208 + -3x = -40 + x + x + x + x + x Combine like terms: x + x = 2x 208 + -3x = -40 + 2x + x + x + x Combine like terms: 2x + x = 3x 208 + -3x = -40 + 3x + x + x Combine like terms: 3x + x = 4x 208 + -3x = -40 + 4x + x Combine like terms: 4x + x = 5x 208 + -3x = -40 + 5x Solving 208 + -3x = -40 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 208 + -3x + -5x = -40 + 5x + -5x Combine like terms: -3x + -5x = -8x 208 + -8x = -40 + 5x + -5x Combine like terms: 5x + -5x = 0 208 + -8x = -40 + 0 208 + -8x = -40 Add '-208' to each side of the equation. 208 + -208 + -8x = -40 + -208 Combine like terms: 208 + -208 = 0 0 + -8x = -40 + -208 -8x = -40 + -208 Combine like terms: -40 + -208 = -248 -8x = -248 Divide each side by '-8'. x = 31 Simplifying x = 31
| 3x+36=10x-48 | | y=25x-7 | | x^4+4x^3+1=0 | | 8(m-1)-7(m+3)=-29 | | 3x+108=9x-12 | | -5x-3(-x+1)=7 | | N+6=-44 | | 107-7x=29x+23 | | 2x/4=6*3 | | 150-5x=22x+18 | | -6x-6(-4x-11)=12 | | 12x^2-40=17x | | (x-7)=(x+3) | | y=-4(-2)-5 | | 23=m-9 | | 7.31=d+3.31 | | 5x+2x=55 | | 2-7x=1-6x | | x^2-15*8= | | x^3-10x^3+21x=0 | | 12x+11=119 | | y=-2-2-3-2-4 | | (6*2-4)/2 | | x-9y=-21 | | 8+3x/5=x | | x^2-11x+30x=0 | | (15*2x)(8*2x)-15*8= | | 3/10(24/130) | | 55-21=m | | 3x^2-21x=-6x^2-5x-7 | | 3/1024/130= | | 1/3+2/5=11/x |